THE ROLE AND PROSPECTS OF DIGITAL EDUCATION TECHNOLOGIES IN TEACHING BIOCHEMISTRY IN HIGHER MEDICAL EDUCATION INSTITUTIONS (European Journal of Interdisciplinary Research and Development, 2026)
This article analyzes the future role of electronic manuals based on artificial intelligence (AI), virtual and augmented reality (VR/AR) technologies in teaching biochemistry. Such adaptive platforms make it possible to create individual learning trajectories tailored to each student's level of knowledge. As a result, digital tools significantly increase students' activity, independent learning skills, and the effectiveness of mastering the subject. The widespread implementation of these technologies in medical higher education institutions and their continuous updating are evaluated as an important condition for training modern, competent physician-researchers.